Uwilgotnienie gruntów pogórniczych w suchych i ciepłych latach hydrologicznych = Moisture on postmining grounds in the dry and hot hydrological years - Stachowski, Piotr; Szafrański, Czesław; Kozaczyk, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the results of field research and observation carried out on experimental areas located at the inner waste heap of the "Kazimierz Północ" open pit. The results show that the highest water reserves exceed half of the water capacity of the postmining grounds profiles and occured from November to April.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zapasy wody w gruncie; niedobory wody; grunt pogórniczy; water deficit; water reserves; postmining grounds